Konversi Lahan Pertanian dalam Pembangunan Infrastruktur PSN (Proyek Strategis Nasional): Analisis Hukum Tata Ruang dan Pengadaan Tanah Tol Probowangi - Kodrat Insany Taqwim (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The construction of the Probolinggo–Banyuwangi Toll Road (Probowangi) as part of Indonesia’s National Strategic Projects (Proyek Strategis Nasional/PSN) reflects a complex interaction between spatial planning law, agricultural land protection, land acquisition regimes, and the doctrine of public interest. This study aims to analyze the implementation of spatial planning law in the Probowangi Toll Road project, examine the legal implications of agricultural land conversion, and assess the juridical justification of public interest within the PSN framework. This research employs normative legal research using statutory, conceptual, and case approaches. The findings reveal a normative tension between Law No. 26 of 2007 on Spatial Planning, Law No. 41 of 2009 on Sustainable Agricultural Land Protection (LP2B), and Law No. 2 of 2012 on Land Acquisition for Public Interest, particularly concerning the conversion of productive agricultural land. The administrative reinforcement of PSN acceleration through Ministerial Regulation No. 16 of 2025 strengthens central government intervention but potentially reduces regional authority in spatial control. This study argues that regulatory harmonization is essential to ensure that infrastructure development aligns with principles of spatial justice, food security, and protection of land rights.